Synthesis and characterization of ferrocene end-capped poly(?-caprolactone)s by a combination of ring-opening polymerization and click chemistry techniques - Eren, Oktay; Gorur, Mesut; Keskin, Bahadir; Yilmaz, Faruk (Elsevier, 2013)
Ferrocene (Fc) end-capped linear and star-shaped poly(epsilon-caprolactone)s (PCLs) with different numbers of arms were synthesized by a combination of ring-opening polymerization (ROP) and click chemistry techniques in a four-step reaction procedure. In the first step, the polymer backbones were prepared via ROP of the a-caprolactone (epsilon-CL) monomer in bulk by employing the compounds with different numbers of hydroxyl groups as the multisite initiators and stannous octoate (Sn(Oct)(2)) as the coordination-insertion catalyst. The hydroxyl end-groups of the obtained PCLs were then converted into a bromides and azides consecutively. In the final step, the Fc moiety was attached to the termini of the PCLs using a Cu(I)-catalyzed 1,3-dipolar cycloaddition reaction between the azide end-groups of the PCLs and the acetylene group of ethynylferrocene under ambient conditions. In all cases, the FT-IR and H-1 NMR spectra indicated a successful and quantitative transformation of the desired end-functional groups. The electrochemical properties of the Fc end-capped PCLs were also investigated via cyclic voltammetry (CV). (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Ferrocene; Poly(epsilon-caprolactone); Ring-opening polymerization; Click chemistry; Star polymers